Evaluating the Impact of Community Experience on Purchase Intention in Online Knowledge Community - Zhao, Hong; Shi, Qiaohong (Frontiers in Psychology, 2022)
Community experience has an important influence on the brand building of online knowledge community. By enhancing the community experience of members, it can promote the building of online knowledge community and the increase of users' purchase intention. Although existing research has explored the influence model of community experience, there is a dearth of research on the influence of community experience on purchase intention. To this end, this study uses the online knowledge community experience as a theoretical basis to construct a mediating model to examine the behavioral patterns of consumers using online knowledge community and to explore in detail the mechanisms of the different dimensions of the community experience on purchase intention. It was found that not only the three dimensions of community experience (i.e., infor-mation experience, entertainment experience, and interactive experience) had a significant effect on brand identity, but also brand identity had a significant effect on purchase intention. The study also confirmed that brand identity mediates the relationship between community experience and purchase intention. This study reveals the mediating mechanism of community experience on purchase intention, and helps to effectively guide the innovative management practices of online knowledge community.